KONTRIBUSI SOFT SKILL DALAM MENUMBUHKAN JIWA KEWIRAUSAHAAN - Utomo, Hardi (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2010)
It was shocking the world of education in Indonesia when it was announced the results of research from Harvard University, United States (U.S.). The study revealed that upon the success a person is not determined solely by the knowledge and technical skills (hard skills), but by the skills of managing self and others (soft skills). This study revealed, success is determined only approximately 20% with the hard skills and the remaining 80% with the soft skills. Interpersonal skills are also owned by an entrepreneur, in order to do creative tasks. Creativity essential elements, exist and the development of a business. In Indonesia alone, the diversity of business and number of wirausahawannya not counted in the United States or in another country. Approximately 0.18% of the entrepreneur, therefore it is necessary to develop soft skills in order to foster the entrepreneurial spirit. Keywords: Soft Skill, Kewirausahaan